REKAYASA DAN UJI PERFORMAN-SI KOMPOR LPG BERTEKANAN DENGAN TUNGKU SERBUK KAYU PADA PRODUKSI GULA KELAPA KRISTAL - Abdul Mukhlis Ritonga; Mustaufik Mustaufik; Andrian Andrian (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2022)
Crystal coconut sugar is a local Indonesian food product that has enormous potential, not only domestically but also abroad. The temperature and cooking time in the production of ant sugar are things that need to be considered because they are related to the efficiency and quality of ant sugar products. Therefore, the required fuel has a high-efficiency value so as to produce high-quality ants. This study aims to compare the performance and energy efficiency as well as the quality of ant sugar products produced from cooking sap using a pressurized LPG stove with a sawdust-fueled stove. Parameters measured include temperature and production time, production rate, yield, fuel consumption rate, fuel demand, fuel cost, energy efficiency, physicochemical and sensory parameters. The method used in this research is an experimental method with the object of research namely coconut sap. Coconut sap used from coconut plantations in Gandatapa Village. From the data analysis carried out, the results showed that the sap cooked with a pressurized LPG stove had a higher energy efficiency (43.29%) compared to the sawdust-fueled stove (13.83%), but in terms of the quality produced using the stove LPG NPSO and furnace can produce granulated sugar with quality standards according to SNI 01-3743-1995.